Karina Grömer with contributions by R. Hofmann-de Keijzer and H.R. Mautendorfer, The Art of Prehistoric Textile Making. The Development of Craft Traditions and Clothing in Central Europe. - Sarri, Kalliope (Journal of Greek Archaeology, 2023)
pp. 533. Vienna: Naturhistorisches Museum, 2016. ISBN-10 3902421940; ISBN-13 978-3902421944. €59.00.